Intra-test reliability of the countermovement push-up and its relationship with anthropometric parameters in semi-professional kickboxers - Pablo Merino-Muñoz; Felipe Guimarães Teixeira; Jorge Perez-Contreras; Felipe Inostroza-Rios; Aleksandro Ferreira; Ciro Brito; Bianca Miarka; Esteban Aedo Muñoz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Objective: This study aimed to investigate the intra-test reliability of countermovement push-up (CMPU) in semi-professional kickboxing athletes and to analyze the association with anthropometric measurements of the upper limb. Methods: 8 semi-professional kickboxing athletes (7 male and 1 female athletes) underwent a series of assessments, including skinfold thickness, limb circumference measurements, and the CMPU test with force platforms. Intraclass correlation coefficients (ICC) and coefficients of variation (CV%) were calculated for CMPU variables. Additionally, Spearman correlation coefficients were computed to assess the relationship between upper limb anthropometric data and CMPU variables derived from the force platform. Results: The ICC and CV% values indicated that the analyzed performance variables exhibited reliability ranging from poor to excellent (ICC = 0.65–0.77, CV% = 5.6–20.8). Push-off time and rate of power development concentric demonstrated unclear reliability (ICC = 0.15–0.31, CV% = 7.5–14.9), while rate of force development braking showed poor to good reliability (ICC = 0.44, CV% = 27.4). Strong to very strong correlations were observed between relaxed arm circumference, contracted arm circumference, forearm circumference, bicipital fold, and concentric impulse, peak force, and peak power. Conclusion: The results of this study emphasize the reliability of CMPU testing in semi-professional kickboxing athletes, making it a potentially valuable tool for monitoring upper limb force and power variables. Additionally, the robust correlations suggest that variations in upper limb circumference can significantly influence force and power generation during the CMPU test. These findings have implications for training program design and performance assessment in activities reliant on upper body strength and power, such as kickboxing.